Real-world observations and impacts of Chinese herbal medicine for migraine: results of a registry-based cohort study - Lyu, Shaohua; Zhang, Claire Shuiqing; Zhang, Anthony Lin; Guo, Xinfeng; Hua, Rong; Mao, Zhenhui; Su, Qiaozhen; Xue, Charlie Changli; Sun, Jingbo (Frontiers in Pharmacology, 2024)
Migraine is a prevalent, recurrent condition with substantial disease burden.Chinese herbal medicine (CHM) has been used frequently for migraine in controlled clinical settings. This study is to summarise the characteristics of patients who seek clinical care in a tertiary Chinese medicine hospital in China; to gather their preferences and values of using CHM; to explore the effect of CHM for migraine and its comorbidities in a real-world setting, and to collect first-hand expertise of clinicians' practice pattern in prescribing CHM for migraine.This registry-based cohort study was prospectively conducted at Guangdong Provincial Hospital of Chinese Medicine from December 2020 to May 2022. Adult migraine patients seeking their initial anti-migraine clinical care at the hospital were consecutively recruited and followed up for 12 weeks. Practitioners specialised in headache management prescribed individualised treatments without research interference. Standardised case report forms were employed to gather information on patients' preferences and perspective of seeking clinical care, as well as to assess participants' migraine severity, comorbidities, and quality of life, at four-weeks intervals. Various analytical methods were utilised based on the computed data.In this study, we observed 248 participants. Of these, 73 received CHM treatment for 28 days or longer. Notably, these participants exhibited a greater disease severity, compared to those treated with CHM for less than 28 days. Of the 248 participants, 83.47% of them expected CHM would effectively reduce the severity of their migraine, around 50% expected effects for migraine-associated comorbidities, while 51.61% expressing concerns about potential side effects. CHM appeared to be effective in reducing monthly migraine days and pain intensity, improving patients' quality of life, and potentially reducing comorbid anxiety, with a minimum of 28 days' CHM treatment. Herbs such as gan cao, gui zhi, chuan xiong, fu ling, bai zhu, yan hu suo, etc. were frequently prescribed for migraine, based on patients' specific symptoms.CHM appeared to be beneficial for migraine and comorbid anxiety in real-world clinical practice when used continuously for 28 days or more.The study has been registered in the Chinese Clinical Trial Registry (No. ChiCTR2000041003).